Passenger's Perception of Services of PT. Indonesian National Shipping Bima Branch: Rifai - Rifai; Nike Ardiansyah; Taufik Irfadat (CV. AFDIFAL MAJU BERKAH, 2022)
Bima port is a vital necessity. The progress of crossing transportation in Bima port encourages the smooth flow of goods and services. The port of Bima since the Dutch colonial era has been known as a gateway for people to enter and leave various regions in the country. Various activities for distributing basic food items are increasingly massive and intensive, making it easier to provide food, board and clothing stocks in the Bima area. As a port, this area is quite strategic in supporting sea transportation and the distribution of goods and services for the local government and the people of Bima. The method used is descriptive quantitative with a population of all employees and the public who receive services, the number of samples is 30 random sampling respondents. As a result, 13.15% of respondents answered that they were very satisfied that the distribution of basic food items was getting more massive, then 44.85 percent of respondents answered that they were satisfied, and respondents who answered quite satisfied were 42.00% and respondents who answered dissatisfied were 0.00%. Bima Port supports sea transportation and the flow of goods and services distribution for the local government and Bima community